Penggunaan Aplikasi Quizizz Paper Mode sebagai Media Alternatif Evaluasi Pembelajaran Al-Qur’an dan Hadis di Madrasah Tsanawiyah - Nurhusni, Firgina Amelia; Tarsono, Tarsono; Nugraha, Mulyawan Sofwandy (ISLAMIKA, 2024)
A crucial aspect in the learning process is evaluation. An effective evaluation system will encourage teachers to design better teaching strategies and provide motivation to students to achieve better learning progress. So the evaluation tools used are very influential on students. The aim of this research is to find out how the Quizizz paper mode application is used in evaluating Al-Qur'an and Hadith learning. This research was conducted at one of the Tsanawiyah Madrasahs in Ujung Berung, Bandung City. The research method used is qualitative with a descriptive approach. The results of this research are that the use of the Quizizz paper mode application in learning evaluation requires stable internet access, the use of an LCD projector, QR print out results which will later be scanned by the teacher. The impact that arises from using this application is that students are very enthusiastic and can foster a competitive spirit. However, negative impacts arise when students are noisy and easy to cheat during the learning evaluation.